Bond Performance of the Rubber particles in the Self-Compacting Concrete - Emiroğlu, Mehmet; Yıldız, Servet; Keleştemur, Oğuzhan; Keleştemur, M. Halidun (My University, 2012)
Generating more ductile concrete elements by using waste tire rubbers have been studied for thirty years. Researchers have been produced a lot of rubberized concrete from low strength structure applications to self-compacting concretes having high strength and durability. It is possible to have more flexible concrete while using the fiber shaped waste tire rubbers. Critical problem of use of these rubbers is poor adherence between rubbers and cement paste interface. It is assumed that use of pozzolans with the Portland cement will fix this adherence problem. Therefore, waste tire rubbers have been studied in the self-compacting concrete in order to enhance the problem. Portland cement, grand granulated furnace slag and pozzolanic cement were used together for preparing the self-compacting concretes. Bonding performances of waste tire rubbers and reinforced bars in the self-compacting rubberized concrete were investigated experimentally in this study.
Bildiri - Yayımlanmış
Keywords: Rubber particles